Synergistic interaction between PPAR ligands and salbutamol on human bronchial smooth muscle cell proliferation. (18th December 2012) - Fogli, S; Stefanelli, F; Picchianti, L; Del Re, M; Mey, V; Bardelli, C; Danesi, R; Breschi, MC
Abstract : Background and Purpose: An important objective in asthma therapy is to prevent the accelerated growth of airway smooth muscle cells which leads to hyperplasia and bronchial hyperreactivity. We investigated the effect of combination of salbutamol and PPARγ agonists on growth factor‐stimulated human bronchial smooth muscle cell (BSMC) proliferation. Experimental Approach: Synergism was quantified by the combination index‐isobologram method. Assays used here included analyses of growth inhibition, cell viability, DNA fragmentation, gene transcription, cell cycle and protein expression. Key Results: The PPARγ gene was highly expressed in BSMC and the protein was identified in cell nuclei. Single‐agent salbutamol or PPARγ agonists prevented growth factor‐induced human BSMC proliferation within a micromolar range of concentrations through their specific receptor subtypes. Sub‐micromolar levels of combined salbutamol‐PPARγ agonist inhibited growth by 50% at concentrations from ∼2 to 12‐fold lower than those required for each drug alone, without induction of apoptosis or necrosis. Combination treatments also promoted cell cycle arrest at the G1/S transition phase and inhibition of ERK phosphorylation. Conclusions and Implications: The synergistic interaction between PPARγ agonists and β2 ‐adrenoceptor agonists on airway smooth muscle cell proliferation highlights the anti‐remodelling potential of this combination in chronic lung diseases.